2009
DOI: 10.1016/j.ijdevneu.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate treatment alters fetal cerebellar gene expression responses to hypoxia

Abstract: Prenatal perturbation of brain circulation and oxygenation is a leading cause of perinatal brain damage affecting about 0.3-0.9% of births. Hypoxia-ischemia (HI) in preterm human infants at gestational week 23-32 results in neurodevelopmental abnormalities in childhood, presenting as learning disability, seizure activity, motor impairment and in the most severe cases, death. Here, we examined the potential of MgSO4 treatment, prior to foetal hypoxia, to attenuate hypoxia induced damage in a murine model of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The possible mechanism may be mainly due to the fact that MgSO 4 can bind to the magnesium site on N -methyl- d -aspartate (NMDA) glutamate channels, inhibiting free radical production, and stabilizing the cell membrane [72,73,74,75]. There is now evidence from meta-analyses of randomized controlled trials that antenatal administration of MgSO 4 is associated with a small but significant reduction in the risk of cerebral palsy and gross motor dysfunction after preterm birth [76,77].…”
Section: Clinical Strategies Of Antioxidants In Hiementioning
confidence: 99%
“…The possible mechanism may be mainly due to the fact that MgSO 4 can bind to the magnesium site on N -methyl- d -aspartate (NMDA) glutamate channels, inhibiting free radical production, and stabilizing the cell membrane [72,73,74,75]. There is now evidence from meta-analyses of randomized controlled trials that antenatal administration of MgSO 4 is associated with a small but significant reduction in the risk of cerebral palsy and gross motor dysfunction after preterm birth [76,77].…”
Section: Clinical Strategies Of Antioxidants In Hiementioning
confidence: 99%
“…Over the last decade, and particularly within the last 3 years, researchers have begun focusing their attention on genomic approaches to investigate brain ischemia and physiological responses to it (Jin et al, 2001; Büttner et al, 2008; Meschia, 2008; Qin et al, 2008; Juul et al, 2009; Grond-Ginsbach et al, 2009; Haramati, 2009; Nakajima, 2009; Popa-Wagner et al, 2009; Yao et al, 2009; Di Pietro et al, 2010; Pruissen et al, 2009; Stamova et al, 2010; Zhan et al, 2010). These studies have shown the importance of high-throughput transcript profiling, such as the DNA microarray technique (DeRisi et al, 1997), for gaining insight into the ischemic brain.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, most animal studies show that exposure to hypoxia is associated with decreased reelin expression in the brain (Golan et al 2009;Haramati et al 2010;Komitova et al 2013;Pillai 2014, 2016;Nisimov et al 2018).…”
Section: Effects Of Hypercapnic Hypoxiamentioning
confidence: 94%